ARTISANAL AND SMALL-SCALE MINING (ASM) AND SUSTAINABILITY, AND IMPROVED LIVELIHOODS. A CASE STUDY OF EAST AFRICAN COUNTRIES (EAC) REGION - ABDINOOR, MAALIM HUSSEIN, (IJRDO - Journal of Business Management, 2025)
Artisanal and small-scale mining (ASM) has experienced explosive growth in recent years due to the rising value of mineral prices and the increasing difficulty of earning a living from agriculture and other rural activities, in that regard the Mining Industry has contributed to the major sources of income and employment for the East African countries, especially the local people of Kenya. Artisanal and Small-Scale mining effects in were studied using structured questionnaires. This research draws on primary data collected from households and artisanal miners. The questionnaire was designed to answer the following questions about the socio-economic impacts of small-scale mining on local community livelihoods in East Africa Countries. Furthermore, the research employs of a descriptive survey design, to understand the effects of mining in the study region. Results indicate that overdependence on mining and poor diversification of livelihood options has hindered the development of rural communities in the region.The equitable distribution of employment opportunities and revenue from small-scale mining remains a challenge for sustainable local development.